A Comparison between Topical application of Calcipotriene, Clobetasol and a combination regime of the two drugs in the treatment of Iraqi Patients with Psoriasis Vulgaris - Matloob, Nadheer. A.; AL-Saadi, Rabab N. (Journal of the Faculty of Medicine Baghdad, 2007)
Back ground: Psoriasis is a chronic relapsing disorder with no life long cure, many systemic and topical modalities are available, one of these topical modalities is the vitamin D analogue(calcipotriene) which is widely used recently to treat psoriasis and many other skin problems.Aim of the study: Is to compare the safety, the efficacy and the tolerability of tolerability of topical calcipotriene, topical clobetasol and both of them in combination in treating Iraqi patients with psoriasis vulgaris. (The first study in Iraq that uses calcipotriene ointment in treating psoriasis and comparing it with other known topical treatments that were commonly used to treat this problem).Patients and methods A total of 128 patients with stable plaque psoriasis (72 males and 56 females) with ages between 13 and 68 years and a mean age of 36 years were included in thisstudy, the patients put in four groups: the first one was treated with calcipotriene ointment only, the second was treated with clobetasol ointment only, the third was treated with both drugs in combination and the fourth was treated with Vaseline ointment as placebo. The patients were fully assessed clinically before, during and after the treatment.Results: The study showed that the combination therapy was more effective than calcipotriene or clobetasol alone as it significantly reduced the mean percentage of PASI score within two weeks of treatment (in 55.9 %, 42.5% and 31.9% of the patients respectively) , the study also showed that the combination therapy had a significantly faster response and a slower relapse rate than that of each drug alone and the effect of calcipotriene appeared to be faster in patients who had no previous treatments.Conclusion:Calcipotriene ointment is a relatively safe, a moderately effective and a well tolerated drug, however, its combination with a potent (very potent) topical corticosteroid will lead to better therapeutic results than the use of each one of them alone.